2005
DOI: 10.1007/s00296-005-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the pathophysiology of fibromyalgia: the potential role of oxidative stress and nitric oxide

Abstract: Fibromyalgia (FM) is a common chronic pain syndrome with an unknown etiology. Recent years added new information to our understanding of FM pathophysiology. Researches on genetics, biogenic amines, neurotransmitters, hypothalamic-pituitary-adrenal axis hormones, oxidative stress, and mechanisms of pain modulation, central sensitization, and autonomic functions in FM revealed various abnormalities indicating that multiple factors and mechanisms are involved in the pathogenesis of FM. Oxidative stress and nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 118 publications
0
63
1
6
Order By: Relevance
“…The polyphenols in OPC have shown beneficial antioxidant effects on oxidative-stress-associated diseases. It has been suggested that oxidative stress plays an important role in the pathobiology of FM [1,7,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyphenols in OPC have shown beneficial antioxidant effects on oxidative-stress-associated diseases. It has been suggested that oxidative stress plays an important role in the pathobiology of FM [1,7,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal sensitization and temporal summation of second pain (windup) have been described in patients with FM [35]. Oxidative stress and nitric oxide may play an important role in FM pathophysiology, however it is still not clear whether oxidative stress abnormalities documented in FM are the cause or the effect [1,7,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These agents seem to act as initiators of an oxidation reactions cycle which is not totally counteracted by the antioxidant defences. This may be a potential cause of the development of FM and also of chronic fatigue syndrome (CFS) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Transaldolase is an enzyme of the non-oxidative phase of the pentose phosphate pathway, which is involved in the generation of reduced nicotinamide adenine dinucleotide phosphate (NADPH). There is a lot of evidence have shown that oxidative stress and nitric oxide may play an important role in fibromyalgia pathophysiology (Ozgocmen et al, 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%